ANALISIS TINDAK TUTUR WACANA HUMOR AGAMA-AGAMA DI INDONESIA - Jupriono, Jupriono; Andayani, Ambar (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
Abstract. The colorful and dynamic relation between religious people in Indonesia arises not only various differences of perception, point of view, and social conflict even terrorism, but it also grows religious humor in social interaction. Religious humor includes exclusive-esoteric humor and inclusive-exoteric humor. Exclusive-esoteric humor is dominated with human perception which views that belief, ritual service and social praxis of other’s are wrong, strange and shallow. Inclusive-exoteric humor is properly in the form of paradox, parody and satire of social attitude from the leader of a religion. The quality of humor from exclusive-esoteric as well as inclusive-exoteric are built by violating speech act norms in common, the cooperative principle, politeness principle, and pragmatic parameter which operate in communication of religious people in daily social interaction. Keywords: humor discourse, exclusive-esoteric humor, inclusive-exoteric humor, speech act, pragmatic parameter.